Implementing Backup and Recovery: The Readiness Guide for the Enterprise - Little, David B. (John Wiley & Sons, 2011)
This guide takes readers through the necessary steps of deploying services by showing how to address the architecture, limitations, and capabilities of the existing network infrastructure